Growth and survival responses of a tropical Daphnia (Daphnia lumholtzi) to cell-bound microcystins - Semyalo, Ronald; Rohrlack, Thomas; Larsson, Petter (Journal of plankton research, 2009)
Eutrophic tropical freshwater bodies often have cyanobacterial blooms that last throughout the year and some of these blooms may produce compounds that are toxic to Daphnia. Nevertheless, tropical species like Daphnia lumholtzi continue to remain abundant in the presence of such blooms. We conducted an experiment on the growth and survival of D. lumholtzi. We fed a toxic cyanobacteria Microcystis aeruginosa PCC 7806 to study the response of D. lumholtzi to cell-bound microcystins. Daphnia lumholtzi showed poor growth and survival in the presence of M. aeruginosa PCC 7806 both with and without microcystins. Survival and growth improved significantly when M. aeruginosa comprised ,50% of the food offered. However, regardless of the amounts of M. aeruginosa in the food, we did not find any significant difference in the growth or survival between the microcystin-containing and the microcystin-lacking treatments. We observed a significant difference in age at maturity between the microcystin-containing and the microcystin-lacking groups when the amount of M. aeruginosa in the food offered was ,50%. The toxic cyanobacteria M. aeruginosa PCC 7806 contains substances other than microcystins that reduce the growth and survival of the tropical D. lumholtzi. However, under low cyanobacteria concentrations and in the absence of microcystins, D. lumholtzi shows improved reproduction rates.
Keywords: Growth; Tropical Daphnia (Daphnia lumholtzi); Cell-bound microcystins